Defective Bile Acid Signaling Promotes Vascular Dysfunction, Supporting a Role for G‐Protein Bile Acid Receptor 1/Farnesoid X Receptor Agonism and Statins in the Treatment of Nonalcoholic Fatty Liver Disease - Silvia Marchianò; Michele Biagioli; Martina Bordoni; Elva Morretta; Cristina Di Giorgio; Valentina Vellecco; Rosalinda Roselli; Rachele Bellini; Carmen Massa; Luigi Cari; Ginevra Urbani; Patrizia Ricci; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background Patients with nonalcoholic fatty liver disease are at increased risk to develop atherosclerotic cardiovascular diseases. FXR and GPBAR1 are 2 bile acid–activated receptors exploited in the treatment of nonalcoholic fatty liver disease: whether dual GPBAR1/FXR agonists synergize with statins in the treatment of the liver and cardiovascular components of nonalcoholic fatty liver disease is unknown. Methods and Results Investigations of human aortic samples obtained from patients who underwent surgery for aortic aneurysms and Gpbar1−/−, Fxr−/−, and dual Gpbar1−/‐Fxr−/− mice demonstrated that GPBAR1 and FXR are expressed in the aortic wall and regulate endothelial cell/macrophage interactions. The expression of GPBAR1 in the human endothelium correlated with the expression of inflammatory biomarkers. Mice lacking Fxr and Gpbar1−/−/Fxr−/− display hypotension and aortic inflammation, along with altered intestinal permeability that deteriorates with age, and severe dysbiosis, along with dysregulated bile acid synthesis. Vasomotor activities of aortic rings were altered by Gpbar1 and Fxr gene ablation. In apolipoprotein E−/− and wild‐type mice, BAR502, a dual GPBAR1/FXR agonist, alone or in combination with atorvastatin, reduced cholesterol and low‐density lipoprotein plasma levels, mitigated the development of liver steatosis and aortic plaque formation, and shifted the polarization of circulating leukocytes toward an anti‐inflammatory phenotype. BAR502/atorvastatin reversed intestinal dysbiosis and dysregulated bile acid synthesis, promoting a shift of bile acid pool composition toward FXR antagonists and GPBAR1 agonists. Conclusions FXR and GPBAR1 maintain intestinal, liver, and cardiovascular homeostasis, and their therapeutic targeting with a dual GPBAR1/FXR ligand and atorvastatin holds potential in the treatment of liver and cardiovascular components of nonalcoholic fatty liver disease.